Analisis Bibliometrik: Kajian "Fasilitasi" dalam Isu Pemberdayaan - Pratama, Luzian; Sari, Nurmala; Pranata, Deni; Shalihin, Nurus; Azwar, Welhendri; Yusuf, M (Jurnal Pemberdayaan Masyarakat, 2023)
Such a massive study of "facilitation" is carried out in discussing issues of community development and empowerment. This article aims to look at the development of articles on facilitation studies in development and empowerment issues. This study was reviewed using a bibliometric approach in which metadata was fully sourced from the Dimension.ai website accessed on January 2, 2023. Metadata related to facilitation studies were searched using the keyword "facilitation" as search input using two filter classifications, namely (a) Document Type "article " (b) Subject Area "human science" which found as many as 2,583 article metadata and stored with the file type Comma Separated Values (CSV). Bibliometric data analysis in this study used VOSviewer software version 1.6.18 for three visualizations (a) visualization of keyword trends (b) visualization of keyword novelty, and (c) visualization of countries. This article finds, first; Facilitation studies in the subject area of human science have been carried out since 1929 by Anderson (1929) under the title An Experimental Study of "Social Facilitation" as Affected by "Intelligence". Second; The article on facilitation studies that was most cited was an article belonging to the Rhodes Team entitled The 'risk environment': a framework for understanding and reducing drug-related harm. Third; there are five clusters related to trending keywords namely "Country" "Group" "Effect" "Cere" and Conflict". This article concludes that the study of facilitation in empowerment issues focuses more on empirical aspects, not much to discuss at the philosophical level.